Peran Perempuan di Sektor Informal Desa Tongke-tonge Kabupaten Sinjai - Mrs. Rosfadiani; Muh. Rizal S. (Rayhan Intermedia, 2022)
This study aims to find out (1) why women play a role in improving family welfare in Tongke-tongke Village, East Sinjai District, Sinjai Regency; (2) The role of women in the informal sector in improving family welfare in Tongke-Tongke Village. (3) Inhibiting factors experienced by women workers in the informal sector in Tongke-tongke Village, East Sinjai District, Sinjai Regency. In this study used a type of qualitative research which was analyzed and written descriptively. Data collection techniques were carried out using observation, interview and documentation methods involving 13 (thirteen) individual informants. Based on the results of the study, it shows that: (1) Women who play a role in improving family welfare are to help increase family income; (2) Apart from acting as a wife and mother, women also play a role in helping their husbands in earning a living, such as selling fish in the market, selling cakes around, selling mixed goods and other informal jobs; (3) Obstacles experienced by women informal workers, namely the division of time between household work and work outside the home so that the form of attention to children is reduced compared to full time at home because time is tight.